Adhesive, barrier layer containing adhesive, high-transparency flexible high-barrier film and packaging and display film material
By using adhesives of epoxycyclohexylsiloxane, aminosiloxane and epoxy-terminal hydroxy polybutadiene in polyvinyl alcohol film forming resins for thermal cross-linking reaction, a three-dimensional silicon structure is formed, which solves the shortcomings of existing polymer film materials in blocking water vapor and oxygen, and achieves high transparency, flexibility and excellent barrier properties.
Patent Information
- Application Number
- CN202411862740.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
Existing polymer film materials have shortcomings in blocking water vapor and oxygen, especially in high-end manufacturing fields such as aerospace and photovoltaic industries, requiring higher transparency, flexibility and barrier properties.
Using an adhesive containing epoxycyclohexylsiloxane, aminosiloxane and epoxy terminal hydroxy polybutadiene, a three-dimensional silicon structure is formed in the polyvinyl alcohol film-forming resin through heat crosslinking reaction, filling the sub-gap, improving water and oxygen resistance, and enhancing the film layer's scratch resistance and low temperature flexibility.
It achieves high transparency, flexibility and excellent water vapor and oxygen barrier properties, while improving the scratch resistance and low temperature flexibility of the film layer, which is suitable for high-end manufacturing fields.
Smart Images

Figure CN119752335A_ABST
Abstract
Description
[0001] Adhesive and barrier layer containing same, highly transparent flexible high barrier film and packaging and display film material Technical Field
[0002] The present invention relates to the technical field of high-functional film materials, and in particular to an adhesive and a barrier layer containing the adhesive, a highly transparent flexible high-barrier film, and a packaging and display film material. Background Art
[0003] Polymer film materials are widely used in various fields. However, due to the molecular gaps between the polymers of polymer film materials, they cannot completely block the passage of water molecules and oxygen molecules with smaller molecular volume. Therefore, in the manufacturing fields of food processing, pharmaceutical packaging, aerospace, photovoltaic industry, new energy batteries, display materials, electronic product packaging, etc., polymer film materials with high barrier properties are required to avoid affecting the performance of the product. In particular, polymer film materials required in high-end manufacturing fields such as aerospace, perovskite photovoltaic products, quantum dot films, and chip manufacturing have particularly high requirements for the barrier properties of small molecules such as water and oxygen, as well as the transparency and flexibility of high barrier film materials. Therefore, there is an urgent need to develop highly transparent flexible film materials with superior water vapor and oxygen barrier properties.
[0004] The methods currently adopted by existing technologies are: Multi-layer composite technology: such as Dutch Shell patent US728,004 19850429 and Jiangsu Woyuan patent CN202220521066.5, which use the technology of multi-layer composite of two or more films with different barrier properties. The multi-layer composite technology delays the time for small molecules to pass through by increasing the diffusion path of small molecules. Small molecules will still penetrate the film layer after long-term use. In addition, the multi-layer composite film is prone to bubbles, cracks, wrinkles and other problems during the production process, which ultimately affect the barrier performance of the film.
[0005] Biaxial stretching technology: such as DuPont EP9840132119980603, which uses biaxial stretching to improve the order of molecular chains and make the stacking more compact, so as to achieve the purpose of blocking small molecules. However, its disadvantage is that after high-temperature biaxial stretching, the crystallization stress in the longitudinal and transverse directions is inconsistent during the cooling process, which easily forms defects of crystal dislocation and loopholes for molecular penetration, resulting in a decrease in barrier performance. Moreover, if only stretching is used, the molecular gaps still exist, and finally the barrier property cannot be guaranteed.
[0006] Coating technology: by coating a barrier layer on the surface of the film, one is to coat metal film, such as CN201821178089.0 barrier film and photovoltaic cell. The barrier property of the film is improved, but the film is opaque and cannot be penetrated by visible light, laser, electron beam, microwave, etc., which affects the later processing; the other is to coat inorganic oxides, such as Japan Toppan Printing (Toppan) CN93120385. Although transparency is achieved, it only relies on inorganic coating, and the barrier performance of the film is still not high, and the inorganic coating is brittle and easily scratched. Summary of the invention
[0007] In order to solve the above problems, the present invention provides an adhesive and a barrier layer, a highly transparent, flexible and high-barrier film and a packaging and display film material containing the same. The adhesive provided by the present application has high epoxy cyclohexyl siloxane activity and good cross-linking properties. Aminosiloxane and epoxy cyclohexyl siloxane components undergo a thermal cross-linking reaction to form a three-dimensional silicon structure in the film layer formed by the polyvinyl alcohol film-forming resin, which effectively fills the molecular gaps of the polyvinyl alcohol film-forming resin, greatly improves the water and oxygen barrier effect, and can also increase the scratch resistance of the film layer formed by the polyvinyl alcohol film-forming resin; the reaction of epoxidized terminal hydroxyl polybutadiene with other components in the adhesive can not only increase the water and oxygen barrier ability of the film layer formed by the polyvinyl alcohol film-forming resin, but also effectively improve the flexibility of the film layer under low temperature conditions.
[0008] The object of the present invention is achieved in the following manner: an adhesive comprises component A: polyvinyl alcohol film-forming resin, component B: aminosiloxane, component C: epoxycyclohexylsiloxane, and component D: epoxidized hydroxyl-terminated polybutadiene.
[0009] Calculated by molar ratio, the optimal ratio of the number of moles of active hydrogen of the amino group to the number of moles of the epoxy group in the adhesive component is 1:1.
[0010] The polyvinyl alcohol film-forming resin is polyvinyl butyral, and the structural formula of aminosiloxane is as follows: The structural formula of epoxycyclohexylsiloxane is as follows: .
[0011] According to the total weight percentage of the sum of component A, component B and component C: component A accounts for 60-90%, and the sum of component B and component C accounts for 10-40%, wherein, calculated by molar ratio, component B: component C ≥ 2; the addition amount of reinforcing resin component D is 1-5% of the total weight of the sum of component A, component B and component C.
[0012] The molecular weight of polyvinyl butyral is 70000-25000, and the acetal degree is 79-93%; The weight average molecular weight of the epoxidized hydroxyl-terminated polybutadiene is 2000-4000.
[0013] The adhesive also contains a diluent, which is an alcohol or ester solvent.
[0014] A barrier layer is formed by coating the above-mentioned adhesive and then thermally crosslinking the adhesive at a temperature of 80-120°C.
[0015] A highly transparent, flexible and high-barrier film comprises, from bottom to top, a polymer substrate, a primer layer, a silicon oxide deposition layer and a barrier layer, wherein the barrier layer is the barrier layer described above.
[0016] The material of the polymer substrate is polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyamide, polyethylene or polypropylene, and the thickness of the substrate is 10-150 μm.
[0017] The base coat layer includes a linear silicon-containing polyurethane resin having no benzene ring structure.
[0018] The silicon oxide deposition layer is a silicon dioxide deposition layer obtained by plasma enhanced chemical vapor deposition, and the thickness of the silicon oxide deposition layer is 40-80 nm.
[0019] The coating amount of the barrier layer is 1-2g / m² and the drying temperature is 80-120℃.
[0020] The linear silicon-containing polyurethane resin without benzene ring structure is a polyurethane adhesive obtained by polymerization of dicyclohexylmethane diisocyanate, polyether diol and double-terminated hydroxyl silicone, and chain extension by dimethylol propionic acid and silanol termination. The coating amount is 1-2g / m².
[0021] The thickness of the silicon oxide deposition layer is 50-60 nm.
[0022] A packaging and display film material, which is a packaging and display material made of the high-barrier film mentioned above.
[0023] Compared with the prior art, the present invention provides an adhesive and a barrier layer containing the same, a highly transparent flexible high-barrier film, and a packaging and display film material. The adhesive provided by the present application has high epoxy cyclohexyl siloxane activity and good cross-linking properties. Aminosiloxane and epoxy cyclohexyl siloxane components undergo a thermal cross-linking reaction to form a three-dimensional silicon structure in the film layer formed by the polyvinyl alcohol film-forming resin, effectively filling the molecular gap of the polyvinyl alcohol film-forming resin, greatly improving the water and oxygen barrier effect, and also increasing the scratch resistance of the film layer formed by the polyvinyl alcohol film-forming resin. The reaction of epoxidized terminal hydroxyl polybutadiene with other components in the adhesive can not only increase the water and oxygen barrier properties of the film layer formed by the polyvinyl alcohol film-forming resin, but also effectively improve the flexibility of the film layer under low temperature conditions. Moreover, after the adhesive of the present application is cross-linked and the barrier layer formed by it, it not only has good water vapor and oxygen barrier properties, but also has high transparency and good flexibility, and has low ultraviolet absorbance, is not easy to yellow, and has good scratch resistance.
[0024] When the adhesive is used as a barrier layer of a highly transparent, flexible and high-barrier film, the aminosilicone and epoxycyclohexylsiloxane components can increase the bonding strength with the silicon dioxide deposition layer.
[0025] The highly transparent, flexible and high-barrier film provided by the present invention is designed to achieve the purposes of high transparency, flexibility and high barrier: a linear silicon-containing polyurethane primer without a benzene ring structure, plasma-enhanced chemical vapor deposited silicon dioxide and a transparent flexible silane epoxy cross-linked barrier layer technology are used to achieve water vapor and oxygen barrier; the linear silicon-containing polyurethane primer without a benzene ring structure has low ultraviolet absorption and does not yellow, and has better transparency and flexibility than a thermally cured primer; the polyurethane primer contains a silicon structure that is beneficial to the subsequent silicon dioxide deposition and increases the fastness of the deposition layer; the silicon dioxide deposition layer is a plasma-enhanced chemical vapor phase silicon dioxide deposition layer, which has high transparency and excellent water vapor and oxygen barrier properties; the barrier layer of the present invention not only has good water vapor and oxygen barrier properties, good transparency and flexibility, but also has a strong bonding force with the silicon dioxide deposition layer and can protect the fragile silicon dioxide deposition layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic structural diagram of the highly transparent, flexible and high-barrier film of the present invention.
[0027] 1. Polymer substrate, 2. Primer layer, 3. Silica deposition layer, 4. Barrier layer. DETAILED DESCRIPTION
[0028] An adhesive comprises component A: polyvinyl alcohol film-forming resin, component B: aminosiloxane, component C: epoxycyclohexylsiloxane, and component D: epoxidized hydroxyl-terminated polybutadiene.
[0029] Aminosiloxane and epoxycyclohexylsiloxane components undergo a thermal crosslinking reaction to form a three-dimensional silicon structure in the film layer formed by the polyvinyl alcohol film-forming resin, effectively filling the molecular gaps of the polyvinyl alcohol film-forming resin, improving the water and oxygen barrier effect, and also increasing the scratch resistance of the film layer formed by the polyvinyl alcohol film-forming resin. The reaction of epoxidized terminal hydroxyl polybutadiene with other components in the adhesive can not only increase the water and oxygen barrier ability of the film layer formed by the polyvinyl alcohol film-forming resin, but also effectively improve the flexibility of the film layer at low temperatures.
[0030] Calculated by molar ratio, the optimal ratio of the number of moles of active hydrogen of the amino group to the number of moles of the epoxy group in the adhesive component is 1:1.
[0031] The polyvinyl alcohol film-forming resin can be polyvinyl alcohol film-forming resin is polyvinyl acetal, preferably polyvinyl butyral. Polyvinyl butyral has excellent film-forming property, high film transparency, good flexibility, better moisture resistance than polyvinyl alcohol, good water vapor and oxygen barrier properties, and good light resistance, heat resistance and cold resistance. It contains a large number of hydroxyl and aldehyde functional groups to form hydrogen bonds with the surface of silicon dioxide, so it has high adhesion to the silicon dioxide interface.
[0032] Component A selects polyvinyl butyral with high molecular weight and high acetalization degree to improve its moisture resistance. The molecular weight of polyvinyl butyral is 70000-250000, and the acetalization degree is 79-93%.
[0033] The structural formula of aminosiloxane is as follows: .
[0034] Component B contains siloxane diamine but does not contain ester bonds and ether bonds. The siloxane bonds have the glass-like transparency of silicone. In addition, the terminal amino groups can react with component C of the adhesive to produce epoxy crosslinking reaction, thereby improving the adhesion and barrier properties of the barrier layer.
[0035] The structural formula of epoxycyclohexylsiloxane is as follows: .
[0036] Component C is tetraepoxycyclohexylsiloxane. Since the epoxy groups connected by four cyclohexyl groups have efficient cross-linking properties, they undergo a stereo cross-linking reaction with the amino groups in component B, the siloxane-containing diamine, which can greatly improve the adhesion and barrier properties of the barrier layer.
[0037] Component B contains siloxane diamine and component C contains tetraepoxycyclohexylsiloxane, which can form a dense silicon-containing film with polyvinyl butyral. Silicon atoms can effectively fill the holes between polyvinyl butyral molecules and effectively prevent the penetration of water vapor and oxygen. At the same time, the barrier layer contains a siloxane structure, which has good affinity with the silicon dioxide deposition layer of the high barrier film, and the barrier layer is not easy to fall off during later use.
[0038] Component D epoxidized hydroxyl-terminated polybutadiene is a reactive liquid rubber with excellent hydrophobicity and low-temperature flexibility. Epoxidized hydroxyl-terminated polybutadiene can undergo cross-linking reaction with aminosiloxane, and has excellent water barrier performance, which enhances the compactness of the film and improves the water vapor barrier of the film layer. At the same time, its elastic butadiene structure can effectively improve the flexibility of the film at low temperatures, which is conducive to the high barrier film still having excellent flexibility when used in extremely cold areas. The weight average molecular weight of component D epoxidized hydroxyl-terminated polybutadiene is 2000-4000.
[0039] The main components of the adhesive are transparent components and have high flexibility.
[0040] The adhesive is composed of component A, component B and component C in the following weight percentages: component A accounts for 60-90%, the sum of component B and component C accounts for 10-40%, and the addition amount of component D is 1-5% of the total weight of the sum of component A, component B and component C.
[0041] In order to facilitate the adhesive to be coated into a film, the adhesive also contains a diluent. The diluent is preferably an alcohol or lipid solvent. The preferred solvent is ethanol, n-propanol, isopropanol, ethyl acetate, butyl acetate, etc., which have very good low toxicity and are environmentally friendly.
[0042] The coating amounts of the high barrier films of the present invention are all grams of solid matter contained in each square meter of the coating film layer, excluding solvent components.
[0043] A barrier layer is formed by coating the above-mentioned adhesive into a film and thermally cross-linking the film.
[0044] The coating amount of the barrier layer is 1-2g / m² and the drying temperature is 80-120℃.
[0045] like Figure 1 As shown, a highly transparent, flexible and high-barrier film comprises, from bottom to top, a polymer substrate 1, a primer layer 2, a silicon oxide deposition layer 3 and a barrier layer 4, and the barrier layer above the silicon oxide deposition layer 3 is the above-mentioned barrier layer.
[0046] First, the polymer substrate of the highly transparent, flexible and high-barrier film of the present invention is described.
[0047] The polymer substrate of the highly transparent, flexible and high-barrier film of the present invention is a film made of organic polymers. They can be single-layer or multi-layer films made of one or more polymer materials by casting, stretching, coextrusion, blow molding and other methods, and necessary functional additives such as plasticizers, antistatic agents, etc. can also be added. The polymer materials include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polyamide (PA), polyimide (PI), polyethylene (PE), polypropylene (PP), polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EVOA), polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), fluorinated polyethylene and other polymer materials. The polymer substrate of the highly transparent, flexible and high-barrier film of the present invention is preferably a film made of polymer materials such as polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyamide, polyethylene, polypropylene, etc. This film material has good flexibility and light transmittance. The thickness of the polymer substrate of the high-barrier film of the present invention is preferably 10-150μm.
[0048] The primer layer of the high barrier film of the present invention is described below.
[0049] The primer layer of the high barrier film can improve the bonding strength between the polymer substrate and the silicon dioxide deposition layer, and at the same time can increase the gas barrier effect of the film material. The primer layer can be selected from acrylic resin, polyester resin, phenolic resin, epoxy resin, polyurethane resin, silane resin, silicone resin, nitrile rubber, etc. The primer layer of the present invention uses a linear silicon-containing polyurethane resin without a benzene ring structure, which is an adhesive prepared from isocyanate and hydroxyl compounds, preferably diisocyanate dicyclohexylmethane and polyether diol (for example, polypropylene glycol PPG (2000) is a polyether diol), double-terminated hydroxyl silicone polymerization, and polyurethane after hydroxymethyl propionic acid chain extension and silanol end-capping. It has good transparency, flexibility and adhesion, does not contain benzene rings, has low ultraviolet absorption, is not easy to yellow, contains polyether segments and silicone, has good barrier properties, and has good fastness to the silicon dioxide deposition layer. The coating amount of the primer layer is 1-2g / m².
[0050] Next, the silicon oxide deposition layer of the highly transparent, flexible and high barrier film of the present invention is described.
[0051] The highly transparent flexible high barrier film of the present invention is provided with a silicon oxide deposition layer. The silicon dioxide film has a series of excellent physical and chemical properties, such as high temperature stability, chemical stability, low permeability, gas barrier properties and other good performance. At the same time, it also has high transparency and low refractive index, which can meet the requirements of the electronics industry for high precision and high transparency. The high barrier film silicon oxide deposition layer of the present invention is a silicon dioxide deposition layer of plasma enhanced chemical vapor deposition. According to the principle of magnetic field confinement of charged particles, plasma enhanced chemical vapor deposition technology uses magnetic field to confine electrons to increase the dissociation rate of gas molecules to achieve the purpose of increasing the deposition rate of thin films. The silicon oxide film is deposited with a mixed gas of organic silicon compounds and oxygen. The selectable organic silicon compounds include hexamethyldisiloxane, tetramethoxysilane, tetraethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, tetramethylsilane, etc., preferably hexamethyldisiloxane. When the thickness of the silicon dioxide deposited layer is less than 30 nm, the gas barrier performance of the film material is significantly reduced. When the thickness of the silicon dioxide deposited layer is greater than 100 nm, the rollability and transparency of the film material are affected. Therefore, the thickness of the gas silicon dioxide deposited layer of the high barrier film of the present invention is 40-80 nm, preferably 50-60 nm.
[0052] Finally, a barrier layer on the highly transparent, flexible and high barrier film silicon oxide deposition layer is described.
[0053] The barrier layer has the characteristics of high transparency and good flexibility: the component polyvinyl butyral has excellent film-forming properties, and the film layer has high transparency and good flexibility.
[0054] Epoxy cyclohexyl siloxane has high activity and good crosslinking properties. Amino siloxane and epoxy cyclohexyl siloxane components undergo thermal crosslinking reactions to form a three-dimensional silicon structure in the film layer formed by the polyvinyl alcohol film-forming resin, effectively filling the molecular gaps of the polyvinyl alcohol film-forming resin, greatly improving the water and oxygen barrier effect, and also increasing the scratch resistance of the film layer formed by the polyvinyl alcohol film-forming resin. The reaction of epoxidized terminal hydroxyl polybutadiene with other components in the adhesive can not only increase the water and oxygen barrier capacity of the film layer formed by the polyvinyl alcohol film-forming resin, but also effectively improve the flexibility of the film layer at low temperatures.
[0055] The adhesive of the present application, after cross-linking, and the barrier layer formed therefrom not only have good water vapor and oxygen barrier properties, but also have high transparency, good flexibility, low ultraviolet light absorption, are not easy to yellow, and have good scratch resistance. The barrier layer is made of transparent components, has high flexibility, and is not easy to yellow.
[0056] When the adhesive is used as a barrier layer of a highly transparent, flexible, high-barrier film, the aminosiloxane and epoxycyclohexylsiloxane components can increase the bonding strength with the silicon dioxide deposit layer. In particular, epoxycyclohexylsiloxane has high activity and good cross-linking properties, which can improve the bonding strength between the barrier layer and the silicon oxide deposit layer and protect the fragile silicon oxide deposit layer.
[0057] The barrier layer of the present invention is usually coated by known techniques in the field, such as knife coating, scraper coating, strip coating, roller coating, press coating, etc., with a coating amount of 0.5-2g / m2 and a drying temperature of 80-120°C.
[0058] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that this embodiment is only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technical personnel skilled in the art can make some non-essential improvements and adjustments based on the above-mentioned contents of the present invention.
[0059] The main raw materials can be obtained from the following companies: Polymer substrates: polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polyamide (PA), polyethylene (PE), and polypropylene (PP) films are all from Xiamen Changsu; Dicyclohexylmethane diisocyanate HMDI comes from Covestro of Germany, polypropylene glycol PPG (2000) comes from Jiangsu Petrochemical Co., Ltd., and double-terminated hydroxyl silicone comes from Guangzhou Slox New Materials Co., Ltd.; tri(tert-pentaoxy)silanol, hexamethyldisiloxane, triethylenediamine, dihydroxymethylpropionic acid, dimethylacetamide and component C tetraepoxycyclohexylsiloxane come from Merck, polyvinyl butyral comes from Butvar® product of Monsanto Company of the United States, component B containing siloxane diamine comes from Aladdin Biochemical Technology Co., Ltd., component D epoxidized terminal hydroxyl polybutadiene comes from Liming Chemical Research Institute, and ethylene glycol methyl ether comes from Jiangsu Tianyin Chemical Co., Ltd.
[0060] Preparation of primer polyurethane adhesive: 26.35g of dicyclohexylmethane diisocyanate, 55g of polypropylene glycol PPG (molecular weight 2000), 5g of double-terminal hydroxy silicone (molecular weight 4000), and 1g of triethylenediamine were added to a 1000 ml four-necked flask with temperature control heating, mechanical stirring, drying tube, condensation reflux and nitrogen protection device, and reacted at 80°C for 3 hours, 120.72g of dihydroxymethylpropionic acid and 93.5g of dimethylacetamide were added, and reacted for 3 hours, and then 24.52g of tri(tert-pentaoxy)silanol was added to react for 2 hours, and the reaction was terminated by cooling. The reaction stock solution was dropped into deionized water containing glacial acetic acid for dispersion, washed with deionized water for multiple times, filtered and dried, and then configured with ethylene glycol methyl ether to form a 10% coating solution. The configured coating solution is the primer polyurethane adhesive, code-named PU.
[0061] Adhesive configuration: Adhesives are usually prepared and used immediately, stored at 5°C, and preferably used within 4 hours. The adhesive codes are N1-N4.
[0062] Adhesive N1: Component A polyvinyl butyral (Butvar® B-90, Mw=70,000-100,000, acetal degree: 79-81%) 90g, component B compound 2.52g, component C compound 7.48g, component D (Mw=4000) compound 1g, diluent is ethanol: ethyl acetate = 1:1 (mass ratio), and the dilution concentration is 20%.
[0063] Adhesive N2: Component A polyvinyl butyral (Butvar® B-76, Mw = 90,000-120,000, acetal degree: 83-93%) 80g, component B compound 5.04g, component C compound 14.96g, component D (Mw = 4000) compound 3g, diluent is n-propanol: ethyl acetate = 1:1 (mass ratio), dilution concentration is 20%.
[0064] Adhesive N3: Component A polyvinyl butyral (Butvar® B-74, Mw = 120,000-150,000, acetal degree: 79-81%) 70g, component B compound 7.56g, component C compound 22.44g, component D (Mw = 3000) compound 4g, diluent is isopropanol: ethyl acetate = 1:1 (mass ratio), dilution concentration is 20%.
[0065] Adhesive N4: Component A polyvinyl butyral (Butvar® B-72, Mw = 170,000-2500,000, acetal degree: 80%) 60g, component B compound 10.08g, component C compound 29.92g, component D (Mw = 2000) compound 5g, diluent is ethanol: butyl acetate = 1:1 (mass ratio), dilution concentration is 20%.
[0066] Manufacturing example of highly transparent flexible high barrier film: Embodiment 1: 1. Corona treatment was applied to the coated surface of the 12 μm polyethylene terephthalate film of the polymer substrate; 2. Apply the above-mentioned primer polyurethane adhesive PU on the corona-treated polymer substrate, with a coating amount of 1g / m²; 3. Plasma enhanced chemical vapor deposition of silica: The corona treated substrate coated with polyurethane adhesive is deposited with silica using a roll-to-roll plasma enhanced chemical vapor deposition device (PECVD): Under the action of the RF electrode in the vacuum chamber, the substrate is activated by argon plasma, and then hexamethyldisiloxane vapor and O2 are introduced. Under the action of the electric arc, hexamethyldisiloxane vapor and O2 react chemically to generate gas-phase silica, which is finally deposited on the substrate. The deposition layer thickness is 55nm.
[0067] 4. Apply adhesive N1 on the silica deposition layer of the polymer substrate after plasma enhanced chemical vapor deposition of silica, the barrier layer coating amount is 1g / m², and the drying temperature is 110℃.
[0068] Embodiment 2-12: Referring to the high barrier film manufacturing process of Example 1, the high barrier films of Examples 2-12 were manufactured by changing the parameters of the polymer substrate, the primer layer, the silicon oxide deposition layer, and the barrier layer according to the data given in Table 1 of the high barrier film manufacturing parameter table.
[0069] Comparative Examples 1-6: Referring to the high barrier film manufacturing process of Example 1, the parameters of the polymer substrate, the primer layer, the silicon oxide deposition layer, and the barrier layer were changed according to the data given in Table 1 to prepare the high barrier films of Comparative Examples 1-6.
[0070] Among them, the preparation of the plasma-free silica deposition layer in Comparative Example 4 is as follows: the substrate that has been corona treated and coated with a polyurethane adhesive is deposited with silica using a roll-to-roll plasma enhanced chemical vapor deposition device (PECVD): the argon plasma is eliminated for the active treatment process of the substrate, and only hexamethyldisiloxane vapor and O2 are introduced. Under the action of the electric arc, the hexamethyldisiloxane vapor and O2 react chemically to generate gas-phase silica, which is finally deposited on the substrate, and the deposition layer thickness is 60nm.
[0071] The performance of the high barrier films in the above embodiments and comparative examples was evaluated according to the following test methods: 1. Determination of film coating thickness: According to the national standard GB / T33051-2016 “Measurement method for thickness of hardened layer of optical functional film surface hardening film”, the thickness was measured using an F20-UV optical film thickness measuring instrument manufactured by Filmetrics, USA.
[0072] 2. Film transmittance (T) determination: According to the national standard GB / T 2410-2008 “Determination of light transmittance and haze of transparent plastics using a haze meter”, the test was performed using the M57D model manufactured by the British DIFFUSION Company.
[0073] 3. Film oxygen permeability (OTR) determination: The oxygen transmission rate (OTR) test method was carried out according to ASTM D3985 standard using the American MOCON OX-TRAN® 2 / 48 oxygen transmission rate analyzer.
[0074] 4. Determination of film water permeability (WVTR): The water vapor transmission rate (WVTR) test method described in ASTM F1249 was used to test the water vapor transmission rate using an American MOCONPERMATRAN-W 3 / 34 WVTR analyzer.
[0075] 5. Determination of film coating adhesion: The adhesion is tested according to the international standard ISO2409 100-grid method. The adhesion is scored on a six-level scale from 0 to 5, with 0 being the worst and 5 being the best.
[0076] 6. Determination of low temperature flexibility of thin film coatings: The film sample was placed in a minus 50°C environment, and a 10cm×10cm film sample was folded 500 times horizontally on both sides using a film bending machine (the front ends of the film sample were folded together in a natural state, and then immediately released, and then the back sides were folded together, and the time for completing one alternating folding of the front and back sides was 0.8 seconds, and each time the front and back folding was completed was counted once). Then the folding direction of the film was exchanged, and the front and back sides were folded 500 times longitudinally, and then its water vapor barrier performance was measured. The scores were scored according to the degree of reduction in the water vapor barrier performance. The scores were divided into 1-10 levels, with 1 being the worst flexibility and 10 being the best flexibility.
[0077] The high barrier film performance evaluation results of the embodiments and comparative examples are shown in Table 2 High Barrier Film Performance Evaluation Table.
[0078] Table 1 High barrier film manufacturing parameters Table 2 High barrier film performance parameters The performance comparison results of the embodiments and comparative examples in Table 2 show that, compared with other high-barrier films, the polymer flexible high-barrier film manufactured by the technology of the present invention can achieve better results in important indicators such as light transmittance, oxygen permeability, water permeability, film adhesion, and low-temperature flexibility. The present invention achieves the purpose through a set of overall solutions: the polymer substrate adopts highly transparent and flexible polymer materials such as polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyamide, polyethylene, and polypropylene; the base coating adopts flexible silicon-based polyurethane without benzene rings, which has good barrier properties and high fastness to the silicon dioxide deposition layer; the silicon oxide deposition layer adopts plasma enhanced chemical vapor deposition silicon dioxide, which has good transparency, adhesion and barrier properties; the barrier layer adopts aminosiloxane, epoxycyclohexylsiloxane, and epoxy terminal hydroxyl polybutadiene cross-linked reinforced polyvinyl butyral adhesive, which not only has good transparency and flexibility, but also silicon atoms can effectively fill intermolecular holes and effectively prevent water vapor and oxygen from penetrating. The silicon cross-linked polyvinyl butyral adhesive also has a strong bonding force with the silicon dioxide deposition layer and can protect the fragile silicon dioxide deposition layer. The film layer after polybutadiene reinforcement has better barrier properties and flexibility under low temperature conditions.
[0079] The high barrier film provided by the present invention has excellent gas barrier properties and water vapor barrier properties, and can be used to manufacture oxygen barrier and water vapor barrier packaging materials, and can be used in the fields of food packaging, pharmaceutical packaging, electronic product packaging, perovskite photovoltaic cell film, quantum dot display film, etc.
[0080] The above description is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. It should be pointed out that for those skilled in the art and any technician familiar with the technical field, without departing from the overall concept of the present invention, the technical solution and the inventive concept of the present invention are equivalently replaced or changed, and several changes and improvements are made, which should also be regarded as the protection scope of the present invention.
Claims
1. An adhesive, characterized in that: The invention comprises component A: polyvinyl alcohol film-forming resin, component B: aminosiloxane, component C: epoxycyclohexylsiloxane and component D: epoxidized terminal hydroxyl polybutadiene.
2. The adhesive according to claim 1, characterized in that: Calculated by molar ratio, the number of moles of active hydrogen of the amino group in the adhesive component: the number of moles of the epoxy group is 1:
1.
3. The adhesive according to claim 1, characterized in that: The polyvinyl alcohol film-forming resin is polyvinyl butyral, and the structural formula of aminosiloxane is as follows: The structural formula of epoxycyclohexylsiloxane is as follows: 。 4. The adhesive according to claim 3, characterized in that: According to the total weight percentage of component A, component B and component C: component A accounts for 60-90%, the sum of component B and component C accounts for 10-40%, and the addition amount of reinforcing resin component D is 1-5% of the total weight of the sum of component A, component B and component C; The molecular weight of polyvinyl butyral is 70000-25000, and the degree of acetalization is 79-93%; The weight average molecular weight of the epoxidized hydroxyl-terminated polybutadiene is 2000-4000.
5. The adhesive according to claim 4, characterized in that: The adhesive also contains a diluent; the diluent is an alcohol or ester solvent.
6. A barrier layer, characterized in that: The barrier layer is formed by coating the adhesive described in claims 1 to 5 and then thermally crosslinking the adhesive, and the thermal crosslinking temperature is 80-120°C.
7. A highly transparent, flexible and high barrier film, comprising, from bottom to top, a polymer substrate, a primer layer, a silicon oxide deposition layer and a barrier layer, characterized in that: The barrier layer is the barrier layer according to claim 6.
8. The highly transparent, flexible and high barrier film according to claim 7, characterized in that: The material of the polymer substrate is polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyamide, polyethylene or polypropylene, and the thickness of the substrate is 10-150 μm; The base coat layer includes a linear silicon-containing polyurethane resin having no benzene ring structure; The silicon oxide deposition layer is a silicon dioxide deposition layer formed by plasma enhanced chemical vapor deposition, and the thickness of the silicon oxide deposition layer is 40-80 nm; The coating amount of the barrier layer is 1-2g / m² and the drying temperature is 80-100℃.
9. The highly transparent, flexible and high barrier film according to claim 7, characterized in that: The linear silicon-containing polyurethane resin without benzene ring structure is a polyurethane adhesive obtained by polymerization of dicyclohexylmethane diisocyanate, polyether diol, and double-terminated hydroxyl silicone, and chain extension by dimethylol propionic acid and silanol termination. The coating amount is 1-2g / m²; The thickness of the silicon oxide deposition layer is 50-60 nm.
10. A packaging and display film material, characterized in that: The packaging and display material is a packaging and display material made of the high barrier film described in any one of claims 7 to 9.
Citation Information
Patent Citations
Multilayered film material
CN1090812A
Barrier film and photovoltaic cell
CN208637436U
Multi-layer co-extrusion high-barrier food packaging film
CN217124237U
Cited By
Water-oxygen barrier coating for flexible OLED (Organic Light Emitting Diode) and flexible OLED packaging film
CN120775480A